Motives and effects of the initial public offerings on the Warsaw Stock Exchange - Tomasz Sosnowski (Institute of Economic Research (IER), 2014)
This paper empirically investigates the links between the motives for going public and changes in the market value and efficiency of new stock companies. Using a sample of 200 firms from Warsaw Stock Exchange between 2005 and 2012 I find that the principal purpose of initial public offering is raising additional capital by the company but divestment grounds of initial shareholders are also important. I find evidence that the sale of secondary shares in the initial public offering may be seen as a negative signal at aftermarket performance of the firm. The data reveal that the most adverse long-term changes in the market value and business efficiency are observed for those companies, where in the initial public offering both primary and secondary shares were sold.
Keywords: G32; G23; 330; initial public offering; Primary shares; Secondary shares; Motives for going public